Isolation and characterization of spontaneously immortalized B‐lymphocyte lines from HIV‐infected patients with and without non‐Hodgkin's Lymphoma. (20th September 2019) - Zhuang, Ke; Zhang, Yongxi; Zhou, Li; Qi, Xiaoying; Xu, Xiqiu; Meng, Fengzhen; Xu, Zhigao; liu, Jinbiao; Shao, Liang; Liu, Huan; Liu, Hang; Fang, Jun; et al.
Abstract: Isolation of viable circulating tumor cells (CTC) holds the promise for improving screening, early diagnosis, and personalized treatment of lymphoma. In this study, we isolated and characterized spontaneously immortalized B‐lymphocyte (SIBC) lines from HIV‐infected patients with and without Non‐Hodgkin's Lymphoma (AIDS‐NHL). A total of 22 SIBC lines was isolated from peripheral blood mononuclear cells (PBMC) of HIV‐infected patients with (n = 40) and without (n = 77) clinically detectable NHL, but not from healthy individuals (n = 34). Of these, 8 SIBC lines named HIV‐SIBC were generated from HIV‐infected patients without AIDS‐NHL (10%, 8/77), while 14 SIBCs named AIDS‐NHL‐SIBC were from 13 of the AIDS‐NHL patients (32.5%, 13/40). Among the 14 AIDS‐NHL‐SIBCs, 12 were derived from AIDS‐NHL patients with poor prognoses (survival time less than 1 year). SIBCs displayed markers typical of memory B cells (CD3 ‐ CD20 + CD27 + ) with EBV infection. Moreover, AIDS‐NHL‐SIBCs were representative of CTC as evidenced by monoclonal Ig gene rearrangement, abnormal chromosomal karyotype, and the formation of xenograft tumors, while HIV‐SIBCs generated harbored some features of tumor cells, none had the capacity of xenograft tumor formation, suggesting HIV‐SIBC present the precursor of CTC. These results indicate that SIBCs is associated with poor prognosis in AIDS‐NHL patients and can be isolated from HIV‐infected patients with NHL and without NHL. This findings point to the need for further molecular characterization and functional studies of SIBCs, which may prove the value of SIBCs in the diagnosis, prognoses, and screening for NHL among HIV‐infected patients. Abstract : Spontaneously immortalized B‐lymphocyte (SIBC) lines were generated by culturing PBMCs from either HIV‐infected patient with or without AIDS‐NHL. SIBCs are representative of the CTCs and associated with poor prognosis in AIDS‐NHL patients, while SIBCs from HIV‐infected patients without NHL could be a precursor of CTC.